Study on the Impact of Site Specific Nutrient Management Technologies in Rice Under Irrigated Domains of Kurnool District of Andhra Pradesh - Ramanaiah, K.V.; Dhanalakshmi, G.; Reddy, G.Rajender; Murthy, A.Krishna; Sudhakar, M. (Asian Journal of Biological and Life Sciences, 2012)
Frontline demonstrations were conducted from 2007 to 2011 in irrigated domains of Kurnool district, Andhra Pradesh to know the usefulness and economic advantage of soil test based nutrient management technology in rice and adoption of integrated nutrient management practices by rice farmers. Five villages were identified and 10 farmers in each of the selected villages were randomly chosen . At the beginning of the demonstrations a base line survey of selected farmers with respect to knowledge and adoption level of different nutrient management practices, rice production costs and productivity levels was carried out. The demonstration of nutrient management technologies covering seven nutrient management practices were conducted in the selected farmer's fields under close supervision of Krishi VIgyan Kendra for a period of five years. After five years, the impact of knowledge and adoption level of soil test based nutrient management technologies and productivity enhancement in rice were assessed. The results clearly indicated that an improvement in knowledge level, adoption level among the selected farmers besides yield advantage and high net income over the existing practice of nutrient application.